Comparison of Clinical Characteristics and Treatment Outcomes of Children Selected for Treatment of Severe Acute Malnutrition Using Mid Upper Arm Circumference and/or Weight-for-Height Z-Score - Isanaka, Sheila (PLoS One, 2015)
OBJECTIVES: Debate for a greater role of mid-upper arm circumference (MUAC) measures in nutritional programming continues, but a shift from therapeutic feeding programs admitting children using MUAC and/or weight-for-height Z (WHZ) to a new model admitting children using MUAC only remains complicated by limited information regarding the clinical profile and response to treatment of children selected by MUAC vs. WHZ. To broaden our understanding of how children identified for therapeutic feeding by MUAC and/or WHZ may differ, we aimed to investigate differences between children identified for therapeutic feeding by MUAC and/or WHZ in terms of demographic, anthropometric, clinical, and laboratory and treatment response characteristics. METHODS: Using secondary data from a randomized trial in rural Niger among children with uncomplicated severe acute malnutrition, we compared children that would be admitted to a therapeutic feeding program that used a single anthropometric criterion of MUAC< 115 mm vs. children that are admitted under current admission criteria (WHZ< -3 and/or MUAC< 115 mm) but would be excluded from a program that used a single MUAC< 115 mm admission criterion. We assessed differences between groups using multivariate regression, employing linear regression for continuous outcomes and log-binomial regression for dichotomous outcomes. RESULTS: We found no difference in terms of clinical and laboratory characteristics and discharge outcomes evaluated between children that would be included in a MUAC< 115 mm therapeutic feeding program vs. children that are currently eligible for therapeutic feeding but would be excluded from a MUAC-only program. CONCLUSIONS: A single anthropometric admission criterion of MUAC < 115 mm did not differentiate well between children in terms of clinical or laboratory measures or program outcomes in this context. If nutritional programming is to use a single MUAC-based criterion for admission to treatment, further research and program experience can help to identify the most appropriate criterion in a broad range of contexts to target children in most urgent need of treatment.